Y Generation and the Job Seeking - Szabó, Katalin; Kelemen, Andrea; Kőmíves, Péter (International Journal of Engineering and Management Sciences, 2017)
Generations Y and their expectations have caused many surprises for employers. They are different compared to their predecessors. Millennials were born in socialism in our country, but they did not experience from it so much, because they grew up in democracy. Their main feature is that they are openminded to opportunities, and they learn quickly modern technology innovations. They have a strong self-conscious, and are highly proactive. They prefer forms of atypical work, because they can carry out their work anywhere in the world due to the internet access. It is very important for them to keep the work - life balance. These properties have overwritten the conventional management methods, such as conventional recruiting techniques. This paper examines the main job seeking features of the Generation Y based on an empirical research.